Comparative effectiveness of bariatric surgeries in patients with obesity and type 2 diabetes mellitus: A network meta‐analysis of randomized controlled trials. (14th April 2020) - Ding, Li; Fan, Yuxin; Li, Hui; Zhang, Yalan; Qi, Dongwang; Tang, Shaofang; Cui, Jingqiu; He, Qing; Zhuo, Chuanjun; Liu, Ming
Summary: A network meta‐analysis of randomized controlled trials (RCTs) was performed to determine the hierarchies of different bariatric surgeries in patients with obesity and type 2 diabetes mellitus (T2DM), in terms of diabetes remission and cardiometabolic outcomes. Seventeen RCTs and six bariatric surgeries, including single anastomosis (mini) gastric bypass (mini‐GBP), biliopancreatic diversion without duodenal switch (BPD), laparoscopic‐adjustable gastric banding (LAGB), laparoscopic sleeve gastrectomy (LSG), Roux‐en‐Y gastric bypass (RYGBP), greater curvature plication (GCP) and nonsurgical treatments (NST) were included. Mini‐GBP, BPD, LSG, RYGBP and LAGB (from best to worst), as compared with NST, were all significantly associated with the remission of T2DM. For the follow‐up period > 3 years, BPD, mini‐GBP, RYGBP and LSG (from best to worst) were significantly superior to NST in achieving the remission of T2DM. For secondary outcomes, the overall ranking for bariatric surgeries was RYGBP > BPD > LSG > LAGB after comprehensively weighting glucose, weight, systolic and diastolic pressure, total cholesterol, triglycerides, high‐density lipoprotein cholesterol (HDL‐C) and low‐density lipoprotein cholesterol (LDL‐C). Mini‐GBP has the greatest probability of achieving diabetes remission in adults with obesity and T2DM, yet BPD was the most effective in long‐term diabetes remission. RYGBP appears to be the most favourable alternative treatment to manage patients with cardiometabolic conditions.